The MHC Associated Peptide Proteomics assay is a useful tool for the non-clinical assessment of immunogenicity - Jankowski, Wojciech; Kidchob, Christopher; Bunce, Campbell; Cloake, Edward; Resende, Ricardo; Sauna, Zuben E. (Frontiers in Immunology, 2023)
The propensity of therapeutic proteins to elicit an immune response, poses a significant challenge in clinical development and safety of the patients. Assessment of immunogenicity is crucial to predict potential adverse events and design safer biologics. In this study, we employed MHC Associated Peptide Proteomics (MAPPS) to comprehensively evaluate the immunogenic potential of re-engineered variants of immunogenic FVIIa analog (Vatreptacog Alfa). Our finding revealed the correlation between the protein sequence affinity for MHCII and the number of peptides identified in a MAPPS assay and this further correlates with the reduced T-cell responses. Moreover, MAPPS enable the identification of "relevant" T cell epitopes and may contribute to the development of biologics with lower immunogenic potential.